Giardia duodenalis Infections in Humans and Other Animals in China - Li, Junqiang; Wang, Haiyan; Wang, Rongjun; Zhang, Longxian (Frontiers in Microbiology, 2017)
Giardia duodenalis is an important zoonotic pathogen in both public and veterinary health, and has been genotyped into at least eight assemblages (A–H), each with a distinct host range. In recent years, this intestinal protozoan parasite has been identified widely in humans and various other animals, and has even been recorded in environmental contaminants. Along with whole genome sequencing of G. duodenalis, multilocus sequence typing is increasingly being used to characterize G. duodenalis isolates. Here, we review the epidemiology, genotyping, and subtyping of G. duodenalis from humans and a wide range of other animals, as well as from wastewater, in China.